Pendampingan Santri untuk Penurunan Tingkat Pelanggaran Lalu Lintas - Mulono Apriyanto; KMS Novyar Sariawan Fikri; Ali Azhar (Universitas Kristen Satya Wacana Salatiga, 2020)
Traffic violations by motor vehicles from 2018-2019 have increased quite rapidly. As an educational institution, the legal science study program cooperates with the traffic department of the Indragiri Hilir resort police to conduct socialization and assistance to students of the Sabilal Muthadin Islamic boarding school as an effort to tackle traffic violations. One of them is by taking precautionary measures to prevent police traffic violations committed by motorized vehicles, providing education about traffic and reminding the public about the importance of respecting traffic signs and installing traffic-related banners. Traffic violations among students in the Kepolisian area of ​​the Indragiri Hiri resort can be brought down after mentoring.